The African Union (AU) and the Regional Economic Communities (RECs): Achievements, Challenges, and Prospects - Clovis, Kalou Zouza Roland; Frejus, Freddy (European Journal of Applied Sciences, 2026)
In the aftermath of the independence of African states, the heads of state of these countries recognized the necessity of establishing a continental organization capable of enabling Africa to assert its presence and influence on the international stage. It was in this context that the Organization of African Unity (OAU) was created on May 25, 1963, later evolving into the African Union (AU) in July 2002 in Durban, South Africa. Between 1975 and 2000, African leaders also developed regional integration frameworks aimed at facilitating the free movement of people and goods, promoting trade, and fostering the harmonious development of the continent. This led to the establishment of the Regional Economic Communities (RECs).However, more than fifty years after the creation of the RECs, their overall performance presents a mixed picture. While some RECs have achieved significant progress toward their objectives, major challenges remain. As key pillars of the African Union’s integration agenda, African RECs have recorded notable achievements in areas such as the free movement of persons and goods, particularly within the Economic Community of West African States (ECOWAS), and financial integration, notably within the West African Economic and Monetary Union (WAEMU/UEMOA) through institutions such as the Regional Stock Exchange (BRVM).Despite these accomplishments, substantial obstacles continue to hinder deeper regional integration, including inadequate infrastructure, political instability, limited industrialization, and low levels of intra-African trade. Addressing these challenges requires stronger institutional capacities, improved regional governance, greater investment in infrastructure, and renewed political commitment from member states. Such efforts are essential for accelerating economic transformation, enhancing regional competitiveness, and achieving the broader objectives of African integration and sustainable development. It is therefore essential to strengthen and accelerate the operational implementation of the African Continental Free Trade Area (AfCFTA) and to enhance infrastructure development aimed at transforming the continent into a single market. African Heads of State must demonstrate strong commitment and make bold decisions with the full participation of their populations. To achieve this, several actions should be undertaken, including the acceleration of economic and trade integration; the development of infrastructure and connectivity; political and institutional reforms; and the strengthening of human capital and the private sector. This study, based on documentary and academic research, has as its primary objective to provide a progress assessment and a comprehensive evaluation of the African Union’s integration instruments, with a view to proposing appropriate recommendations capable of enabling Africa to accelerate its economic, commercial, and regional integration for the benefit and well-being of the African people. This study therefore serves as a decision-making support tool for African leaders, the international community, and all stakeholders committed to supporting Africa, enabling them to take concrete actions toward the continent’s sustainable development.